Pharmacokinetics of 400 mg ropivacaine after periarticular local infiltration analgesia for total knee arthroplasty. Issue 3 (9th January 2017) - Fenten, M. G. E.; Bakker, S. M. K.; Touw, D. J.; van den Bemt, B. J. F.; Scheffer, G. J.; Heesterbeek, P. J. C.; Stienstra, R.
Abstract : Background: Although considered safe, no pharmacokinetic data of high dose, high volume local infiltration analgesia (LIA) with ropivacaine without the use of a surgical drain or intra‐articular catheter have been described. The purpose of this study is to describe the maximum total and unbound ropivacaine concentrations ( C max, C u max ) and corresponding maximum times ( T max, T u max ) of a single‐shot ropivacaine (200 ml 0.2%) and 0.75 mg epinephrine (1000 μg/ml) when used for LIA in patients for total knee arthroplasty. Methods: In this prospective cohort study, 20 patients were treated with LIA of the knee for primary total knee arthroplasty. Plasma samples were taken at 20, 40, 60, 90, 120, 240, 360 min and at 24 h after tourniquet release, in which total and unbound ropivacaine concentrations were determined. Results: Results are given as median [IQR]. Highest ropivacaine concentration ( C max ) was 1.06 μg/ml [0.34]; highest unbound ropivacaine concentration ( C u max ) was 0.09 μg/ml [0.05]. The corresponding time to reach the maximum concentration for total ropivacaine was 312 min [120] after tourniquet release, and for the unbound fraction 265 [110] min after tourniquet release. Conclusion: Although great inter‐individual variability was found between the maximum ropivacaine concentrations, both maximum total and unbound serum concentrations of ropivacaine remained well below the assumed systemic toxic thresholds of 4.3 and 0.56 μg/ml.